Diet type and the oral microbiome - Betancur, Daniel; Jara, Evelyn L.; Lima, Celia A.; Victoriano, Monserrat (Frontiers in Nutrition, 2026)
BackgroundThe oral microbiome changes across the lifespan and is modulated by behavioral and metabolic exposures. Tobacco consumption, suboptimal hygiene, and frequent sugar intake disrupt microbial homeostasis, thereby increasing vulnerability to chronic oral diseases. While diet influences systemic metabolic and inflammatory health, evidence describing persistent, direct ecological effects on oral microbial communities remains limited.ObjectiveThe objective of this study is to synthesize mechanistic insights on how dietary patterns shape the oral microbiome and influence systemic inflammatory or metabolic risk.MethodologyA narrative, non-systematic review was conducted through expansive literature exploration. Peer-reviewed original and clinical studies reporting defined dietary exposures caloric restriction, plant-based diets, inorganic nitrate and fiber intake, and high-fat or high-sugar processed diets, were qualitatively evaluated for mechanistic relevance.Key findingsPlant-enriched, high-fiber diets, nitrate intake, and caloric restriction were associated with reduced oxidative stress, lower pro-inflammatory cytokines, and greater diversity of commensal taxa, suggesting improved ecological stability. In contrast, processed diets promote metabolic conditions that indirectly remodel the oral habitat, favoring dysbiosis and a niche permissive to periodontitis.ConclusionThe diet–oral microbiome–systemic inflammation axis is bidirectional and clinically relevant. Understanding both direct ecological regulation and indirect metabolic effects is essential to support precision nutrition strategies aimed at maintaining oral microbial balance and systemic inflammatory risk mitigation.